A Giant Scrotal Cavernous Hemangioma Extending to the Penis and Perineum: A Case Report - Osman Ergün; Berit Gokce Ceylan; Abdullah Armagan; Nilgun Kapucuoglu; A. Murat Ceyhan; Hakki Perk (Kaohsiung Journal of Medical Sciences, 2009)
Cavernous hemangioma is a congenital, benign vascular tumor that occurs in the deep dermis and subcutaneous tissue. Scrotal hemangiomas are rare entities and are usually diagnosed in childhood. Adult scrotal hemangiomas are also extremely rare. They are infrequently encountered in adults because they are usually removed in childhood. Urologists often face difficulties in deciding surgery to treat a genital cavernous hemangioma. Here, we report a case of scrotal cavernous hemangioma that involved the entire penis and scrotum, and extended to the perineum in a 44-year-old man, and we review the literature.